Analisis Likuiditas, Tax Avoidance, Pertumbuhan Penjualan dan Pertumbuhan Laba Terhadap Nilai Perusahaan: Studi Keuangan pada Perusahaan Subsektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia Tahun 2022 - Resti Yunisa; Dicky Jhoansyah; Kokom Komariah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to find out how the influence of Liquidity, Tax Avoidance, Sales Growth and Profit Growth on Company Value is described. The population in this research is textile and garment sub-sector companies listed on the Indonesia Stock Exchange for the 2022 period. The method used is a quantitative method with an associative descriptive approach. With a total sample of 19 with saturated sampling. Using secondary data collection techniques and descriptive statistical analysis, classic assumption tests with normality test, multicollinearity test, heteroscedasticity test, coefficient of determination, multiple correlation coefficient, multiple linear regression test, partial test (t) and simultaneous test (f). The statistical results of the f test (Simultaneous Test) show that there is a simultaneous and significant influence of the variables Liquidity, Tax Avoidance, Sales Growth, Profit Growth on Company Value. Based on the statistical results of the t test (partial test), liquidity has a negative and significant effect on Company Value. Meanwhile, Tax Avoidance has a positive and insignificant effect on Company Value. Furthermore, Sales Growth has a positive and significant effect on Company Value. And Profit Growth has a negative and insignificant effect on Company Value.